Pengaruh Stres Kerja Terhadap Produktivitas Kerja Pegawai IAIN kendari - Syamsuddin Syamsuddin; Kasim Kasim; Sulistyorini Sulistyorini; Abdul Kadir; Nur Alim (Institut Agama Islam Negeri (IAIN) Kendari, 2020)
This article aims to describe and analyze the influence of occupational stress on the workmanship of employees of IAIN Kendari.This research uses a quantitative approach through causal research. The population of this research is all of IAIN Kendari employees. The total population in this study was 123 people consisting of officers and lecturers who had additional administrative tasks ranging from rectorate level to study program. Determination of the number of samples in this study using the Slovin formula. From the results of the calculation obtained a sample amount of 94 peoples. The results showed that there was a negative impact on work stress on the productivity of IAIN Kendari employees with a coefficient of determination of-0.182 or had an influence of 18.2%. This gives the meaning that working stress will negatively affect the working productivity of IAIN Kendari employees. The results of this research implicates the leadership of IAIN Kendari if they want to increase employee productivity in the form of targets achieved, accuracy of completing work, quality of work, and efficiency of resource utilization by employees can is done by the work of working stress at the employee's level of individuals, groups, and organizations.